(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
he present paper seeks to explain the impact of the Mexican Revolution on the economy of the Southern District of Baja California, concerning the intervention and use of property accumulated by the revolutionary groups. It will be pointed out that it did not extend all the way along the District, neither did it reach all economic sectors, and it responded to political and business payments. Exempt from property control were those owners who stayed in a relatively marginal position in the ight for power, as well as those who showed willingness to support the military faction that dominated the region.